Achieving biocompatible stiffness in NiTi through additive manufacturing. (November 2016) - Taheri Andani, Mohsen; Haberland, Christoph; Walker, Jason M; Karamooz, Mohammadreza; Sadi Turabi, Ali; Saedi, Soheil; Rahmanian, Rasool; Karaca, Haluk; Dean, David; Kadkhodaei, Mahmoud; Elahinia, Mohammad
This article seeks to reduce the stiffness of NiTi parts from a nonporous state to that of human bone by introducing porosity. Compact bone stiffness is between 12 and 20 GPa while the currently used bone implant materials are several times stiffer. While very stiff implants and/or fixation hardware can temporarily immobilize healing bone, it also causes stress shielding of the surrounding bone and commonly results in stress concentrations at the implant or immobilization hardware's fixation site(s). Together these processes can lead to implant or fixation hardware and/or the surrounding bone's failure. Porous NiTi can be used to reduce the stiffness of metallic implants while also providing necessary stabilization or immobilization of the patient's reconstructed anatomy. In this work, mechanical behavior of porous NiTi with different levels of porosity is simulated to show the relation between the stiffness and porosity level. Then porous structures are fabricated through additive manufacturing to validate the simulation results. The results indicate that stiffness can be reduced from the bulk value of 69 GPa to as low as 20.5 GPa for 58% porosity. The simulation shows that it is possible to achieve a wide range of desired stiffness by adjusting the level of porosity.